Opening the doors of learning: Increasing access to music degrees - de Villiers, A. C. (South African Journal of Higher Education, 2022)
This article is contextualized for Music and is a response to the CHE (2013) Report that proposes a flexible curriculum structure for undergraduate degrees in South Africa, to address student under preparedness. Research states that music graduates need well developed identities in music, as well as generic, transferable skills to ensure lifelong employment and that a bachelor of music degree is best suited for this. However, in the South African context, the bachelor of music degree qualification is not accessible to the majority of prospective students as they are under prepared to study music at tertiary level. Only a minority of learners receive quality music education at school, while the majority of learners, including those from low socio-economic communities, do not receive formal music education. Under preparedness to study music, has traditionally been addressed through certificates and diploma qualifications in music. A discussion, and interpretation of the literature, has led to the researcher to develop an alternate framework to both improve student access to music degrees and manage under preparedness. The proposed approach advocates that music departments at universities adopt the framework of the national certificate vocation as an alternative to certificates and diplomas. The alternative curriculum structure for music, would be a more cost effective way to address under preparedness, improve academic success and lead to high skill levels. The study is situated in a constructivist, interpretive worldview, with a qualitative research design. Purposive sampling in the form of the choice of literature for the theoretical framework was adopted. While this theoretical study is contextualized for music, it is applicable to other fields.